Intraoperative CT-Guided Endoscopic Surgery for ICH [ICES] - Vinall, Phil (MD Conference Express, 2013)
This article presents 180-day data from the Intraoperative CT-Guided Endoscopic Surgery trial [ICES] showing that early CT-guided endoscopic surgery is safe and associated with improved neurological outcomes compared with medical management in patients with primary intracerebral hemorrhage. ICES is a substudy of the Minimally Invasive Surgery Plus rtPA for Intracerebral Hemorrhage Evacuation study [MISTIE; NCT00224770].